Identification of single nucleotide polymorphisms in hematopoietic cell transplant patients affecting early recognition of, and response to, endotoxin - Guinan, Eva C (2013)
Hematopoietic cell transplant (HCT) is a life-saving therapy for many malignant and non-malignant bone marrow diseases. Associated morbidities are often due to transplant-related toxicities and infections, exacerbated by regimen-induced immune suppression and systemic incursion of bacterial products. Patients undergoing myeloablative conditioning for HCT become endotoxemic and display blood/plasma changes consistent with lipopolysaccharide (LPS)-induced systemic innate immune activation. Herein, we addressed whether patients scheduled for HCT display differences in recognition/response to LPS ex vivo traceable to specific single nucleotide polymorphisms (SNPs). Two SNPs of LPS binding protein (LBP) were associated with changes in plasma LBP levels, with one LBP SNP also associating with differences in efficiency of extraction and transfer of endotoxin to myeloid differentiation factor-2 (MD-2), a step needed for activation of TLR4. None of the examined SNPs of CD14, bactericidal/permeability-increasing protein (BPI), TLR4 or MD-2 were associated with corresponding protein plasma levels or endotoxin delivery to MD-2, but CD14 and BPI SNPs significantly associated with differences in LPS-induced TNF-α release ex vivo and infection frequency, respectively. These findings suggest that specific LBP, CD14 and BPI SNPs might be contributory assessments in studies where clinical outcome may be affected by host response to endotoxin and bacterial infection.